2022
DOI: 10.3390/ijerph19169995
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in Dementia Management and Its Associated Factors among Primary Care Doctors in Malaysia

Abstract: Primary care doctors (PCDs) play an important role in the early diagnosis and management of dementia. This study aimed to determine the knowledge, attitude, and confidence in managing dementia among PCDs in Malaysia. It also aimed to determine the factors associated with higher confidence levels in dementia management. An online-based cross-sectional study using Google FormsTM was performed. Sociodemographic and work-related data were collected, and Dementia Knowledge among General Practitioners & General … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Descriptive analysis was used to summarize a large amount of data, such as frequencies, percentages, means and standard deviations. Multiple linear regression (Ahmed et al, 2022;Jeong et al, 2022;Sodri et al, 2022) was used to analyse the factors affecting the profit of ACs, and a multinomial logistic regression (Long & Freese, 2001) was used to analyse the factors affecting the choice of agribusiness by ACs. Equation ( 1) represents the multiple linear regression model used in this study (Bond, 2009;Suminah et al, 2022):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive analysis was used to summarize a large amount of data, such as frequencies, percentages, means and standard deviations. Multiple linear regression (Ahmed et al, 2022;Jeong et al, 2022;Sodri et al, 2022) was used to analyse the factors affecting the profit of ACs, and a multinomial logistic regression (Long & Freese, 2001) was used to analyse the factors affecting the choice of agribusiness by ACs. Equation ( 1) represents the multiple linear regression model used in this study (Bond, 2009;Suminah et al, 2022):…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive analysis was used to summarize a large amount of data, such as frequencies, percentages, means and standard deviations. Multiple linear regression (Ahmed et al, 2022; Jeong et al, 2022; Sodri et al, 2022) was used to analyse the factors affecting the profit of ACs, and a multinomial logistic regression (Long & Freese, 2001) was used to analyse the factors affecting the choice of agribusiness by ACs. Equation () represents the multiple linear regression model used in this study (Bond, 2009; Suminah et al, 2022): Yigoodbreak=α0goodbreak+β1X1goodbreak+β2X2goodbreak+β3X3goodbreak+β4X4goodbreak+β5X5goodbreak+β6X6goodbreak+β7X7goodbreak+γ1d1goodbreak+γ2d2goodbreak+γ3d3goodbreak+γ4d4goodbreak+γ5d5goodbreak+γ6d6goodbreak+γ7d7goodbreak+γ8d8goodbreak+γ9d9goodbreak+γ10d10goodbreak+γ11d11goodbreak+εi where Yi is the profit of the i th AC, α 0 is the intercept, β and 𝛾 are the coefficients of the independent variables, X 1 is the number of members, X 2 is the number of staff members, X 3 is the operating capital, X 4 represents an AC having an office, X 5 represents the presence of a compilation business, X 6 represents the presence of a trading business and X 7 represents an AC that provides an average payback.…”
Section: Methodsmentioning
confidence: 99%
“…Primary care physicians play an essential role in detecting and diagnosing dementia in the elderly. They are frequently the first point of contact with older people, so they need a high index of suspicion when encountering patients with memory complaints [ 6 ]. Limitations in healthcare providers' attitudes, knowledge, and communication between patients and their caregivers are significant contributors to missed and late detection and diagnosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Malaysia utilizing GPACS-D reported a mean confidence score of 2.96 (±0.76) among the participants in managing dementia. The study's results revealed that several factors, including dementia knowledge, higher scores for attitudes toward dementia, and prior education on dementia, were significantly associated with higher levels of confidence in managing dementia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following that, the proper pharmacological therapy can be initiated, and psychosocial interventions can be put in place, but numerous studies have found that the prevalence of dementia in primary care settings is low. 3 In the primary care context, dementia is grudgingly reported, inadequately recognized, underdiagnosed, and poorly managed. People with dementia have a fundamental human right to accessible, equitable primary care, even if it is accepted that managing dementia with its gradual cognitive, functional, physical, and psychiatric impairments is complex.…”
mentioning
confidence: 99%